Impacts of the use of alcoholic beverages by nursing professionals and the relationship with work: a theoretical reflection (Research, Society and Development, 2021)
Objective: To describe the impacts of the use of alcoholic beverages by nursing professionals and the relationship with work, based on a theoretical reflection. Methodology: Theoretical essay of a reflective nature, from the literature on the impacts of the use of alcoholic beverages by nursing professionals and the relationship with work, through a non-systematic bibliographic review, with a qualitative approach, on the theme “use of alcoholic beverages by nursing professionals and their relationship with work”. For the literature review, LILACS, CINAHL, BDENF, MEDLINE and Web of Science were used with the referred strategies and time frame from 2010 to 2020, the survey was limited to articles published in Portuguese, English and Spanish. Results: The literature analysis was arranged in two sub-themes: “Impacts of the use of alcoholic beverages by nursing professionals” and “Factors associated with the consumption of alcoholic beverages in the nursing work environment”. Conclusion: The damages that directly affect the quality of care were highlighted, compromising not only patient safety, but causing a problem that affects the entire institutional health system and regarding factors associated with the consumption of alcoholic beverages in the workplace of In nursing, stressors were highlighted, as well as the current health crisis as a result of Covid-19 and social isolation.